PLANKTONIC FORAMINIFERAL BIOSTRATIGRAPHY, MICROFACIES ANALYSIS, SEQUENCE STRATIGRAPHY, AND SEA-LEVEL CHANGES ACROSS THE CRETACEOUS-PALEOGENE BOUNDARY IN THE HAYMANA BASIN, CENTRAL ANATOLIA, TURKEY - Esmeray-Senlet, Selen; Altıner, Sevinç; Altıner, Demir; Miller, Kenneth G. (Journal of Sedimentary Research, 2015)
The Cretaceous-Paleogene (K/Pg) boundary in the Haymana Basin, Central Anatolia, Turkey, was delineated using planktonic foraminiferal biostratigraphy, microfacies analysis, and sequence stratigraphy. An similar to 29 m outcrop consisting of limestone and marl was measured, and four planktonic foraminiferal biozones were identified spanning the boundary. Planktonic foraminiferal extinction across the K/Pg boundary was catastrophic and abrupt. The extinction level is overlain by a unit (Zone P0) showing an increase in echinoid fecal pellets and authigenic clay minerals such as glauconite, suggesting low sedimentation rates in the early Danian. Ten microfacies types were identified indicating inner-ramp to basinal paleoenvironments based on the sedimentological characteristics and microfossil and macrofossil assemblages. Maastrichtian carbonates contain large benthic foraminifera, calcareous red algae, bryozoans, fragments of echinoderms and mollusks, and planktonic foraminifera. Overlying Maastrichtian-Danian silty marls and silty limestones have common planktonic and benthic foraminifera. Progradation of carbonates into the basin took place during the highstand systems tract, and deposition of a silty marl succession occurred during the transgressive systems tract. The K/Pg boundary is in the upper part of the transgressive systems tract, below a maximum flooding surface. Sequence stratigraphic analysis of a second section, Campo Pit, New Jersey, USA, showed that the K/Pg boundary occurs within a transgressive systems tract in New Jersey as well, suggesting a global sea-level rise across the K/Pg boundary.